Vitamin D Levels in Pregnancy with Preeclampsia: A Cross-Sectional Study in The Tropics - Lasiyati Yuswo Yani; Eka Dewi Retnosari (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Biological effect of vitamin D sufficiency has an effect on blood pressure regulation of the renin-angiotensin system which help reducing elevated blood pressure. There is a meaningful difference of vitamin D levels between preeclampsia incidences and normal pregnant women. The purpose of the research is to find out the correlation between vitamin D levels and preeclampsia. Research method used is analytic cross-sectional study with the pregnant women diagnosed with preeclampsia as a population. The sample is 76 people consisting of 38 people of case group and 38 people of control group. The Point-Biserial correlation test is used for result analysis. The result of the research shows that there is no correlation between vitamin D levels and preeclampsia incidences with the p value 0.052. It indicates that vitamin D levels does not correlate with preeclampsia incidence in pregnant women. The finding of the research supports the theory that preeclampsia is influenced by complex etiopathogenesis.